Polyethyleneimine-impregnated alkali treated waste bamboo powder for effective dye removal - Zhang, Jian (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
In this study, the polyethyleneimine (PEI) modified waste bamboo powder (WBP-Na-PEI) was successfully prepared and applied to adsorbing Congo red (CR) dye from aqueous solution. The obtained materials were characterized by field emission scanning electron microscope, X-ray diffraction, Fourier transform-infrared, and thermogravimetric analysis. The results showed that WBP-Na-PEI(1.8 K-5) was synthesized successfully and PEI uniformly covered the WBP-Na-PEI(1.8 K-5) surface. In the process of adsorption, four kinds of influencing factors were discussed, and the adsorption mechanisms such as kinetics, isotherm, thermodynamics were explored. The maximum adsorption capacity of WBP-Na-PEI(1.8 K-5) was 992.94 mg·g-1 at 298 ± 1 K, and the removal efficiency was over 98%. Pseudo-first-order, pseudo-second-order and intra-particle diffusion models were studied, the results showed that the adsorption process conformed to the pseudo-second-order model, and the rate of this process was controlled by many steps. Furthermore, the removal efficiency of the adsorption kinetics reached 85% within 10 minutes. The results of the isotherm model and thermodynamics showed that the adsorption process was consistent with the Langmuir model and was mainly a spontaneous chemical endothermic process of monolayer. And the removal efficiency of the adsorbent reached 93% at the concentration of 400 mg/L, which can be expected to have a broad prospect in the treatment of CR industrial wastewater